The Bo Smith Commission viewed from the other side of the bridge - Sundström, Göran; Lemme, Marja (Politica, 2016)
This article analyzes the Bo Smith Commission’s problem descriptions and solutions regarding state officials’ advice to politicians from a Swedish perspective. It is claimed that the kind of problems that the Commission discusses have not been prominent in Swedish debate or research. The article points at dissimilarities in the two countries’ administrative traditions that might explain this difference. First, there are more politically appointed officials at the top in Sweden than in Denmark. Second, in Sweden there are requirements for collective decision-making in government, while in Denmark there is ministerial rule. And third, the independent agencies and committees in Sweden have a clearly articulated role to provide the government with advice for its decision-making, while the agencies in Denmark do not participate very actively in the advisory work for the ministers.